(untitled) (LACCEI, 2024)
Each country’s metalworking industry has much economic development, providing companies with jobs and new products. However, companies have different problems in improving various aspects such as production, quality, and delivery times, among others. Therefore, to solve these problems, this article proposes a model based on implementing the Lean philosophy using different tools such as 5S, TPM, SLP, and SMED to increase the overall equipment efficiency (OEE). In addition, work was done on the mindset of workers to sensitize them through the ADKAR Model. A pilot test was carried out to validate the improvements, which gave us good results in the qualification of the audits carried out. In addition, a simulation was carried out in which the Arena software was implemented, and the result was an improvement in the OEE index of 17.60%, a reduction of 44.59 meters in operator movements, and an improvement in reducing operator effort by 88.5%. The contribution of this study can guide those responsible for the operations of SMEs in the metalworking industry that the tools of the Lean Manufacturing philosophy implemented together with the ADKAR change management model, are necessary to transform the processes as they complement each other, achieving a reduction in operational waste through the improvement of the mindset of employees by increasing their commitment to continuous improvement.